Defect‐Rich Adhesive Molybdenum Disulfide/rGO Vertical Heterostructures with Enhanced Nanozyme Activity for Smart Bacterial Killing Application. Issue 48 (28th October 2020) - Wang, Longwei; Gao, Fene; Wang, Aizhu; Chen, Xuanyu; Li, Hao; Zhang, Xiao; Zheng, Hong; Ji, Rui; Li, Bo; Yu, Xin; Liu, Jing; Gu, Zhanjun; et al.
Abstract: Nanomaterials with intrinsic enzyme‐like activities, namely "nanozymes, " are showing increasing potential as a new type of broad‐spectrum antibiotics. However, their feasibility is still far from satisfactory, due to their low catalytic activity, poor bacterial capturing capacity, and complicated material design. Herein, a facile synthesis of a defect‐rich adhesive molybdenum disulfide (MoS2 )/rGO vertical heterostructure (VHS) through a one‐step microwave‐assisted hydrothermal method is reported. This simple, convenient but effective method for rapid material synthesis enables extremely uniform and well‐dispersed MoS2 /rGO VHS with abundant S and Mo vacancies and rough surface, for a performance approaching the requirements of practical application. It is demonstrated experimentally and theoretically that the as‐prepared MoS2 /rGO VHS possesses defect and irradiation dual‐enhanced triple enzyme‐like activities (oxidase, peroxidase, and catalase) for promoting free‐radical generation, owing to much more active edge sites exposure. Meanwhile, the VHS‐achieved rough surface exhibits excellent capacity for bacterial capture, with elevated reactive oxygen species (ROS) destruction through local topological interactions. As a result, optimized efficacy against drug‐resistant Gram‐negative and Gram‐positive bacteria can be explored by such defect‐rich adhesive nanozymes, demonstrating a simple but powerful way to engineered nanozymes for alternative antibiotics. Abstract : Molybdenum disulfide/rGO vertical heterostructures are demonstrated to possess triple enzyme‐like activities, which are further enhanced through light irradiation. Coupled with the rough surface that contributes excellent capacity for bacterial capture, preeminent antibacterial efficacy against drug‐resistant bacteria is exhibited both in vitro and in vivo by such a defect‐rich adhesive nanozyme, which will blaze a new path for the development of alternative antibiotics.